The Strange Case of Dr. Jekyll and Mr. Hide - Stevenson, Louis (New York HarperPaperbacks, 1996)
Dr. Henry Jekyll is a respected doctor and scientist whose mesterious behaviour and srtange experiments worry his friends. His exact opposite, Edward Hyde, makes people uneasy with hus destructive and corrupt deeds.
Keywords: Children Literature